Ocular surface changes in the treatment of rosacea: comparison between low-dose oral isotretinoin and doxycycline - Xavier Andrade, Fabio Mendonca; Picosse, Fabiola Rosa; Cunha, Laura Pires da; Valente, Camila Maia; Bezerra, Fernanda Machado; Miot, Helio [UNESP]; Bagatin, Edileia; Freitas, Denise de (Consel Brasil Oftalmologia, 2020)
Purpose: To compare the impact of ocular changes between systemic treatment with doxycycline and low-dose oral isotretinoin in patients with moderate-to-severe papulopustular rosacea. Methods: Patients were randomized to receive either isotretinoin 0.3-0.4 mg/kg (group A) or doxycycline 100 mg/day (group B) for 16 weeks. Ocular symptoms were searched and evaluated, including best-corrected visual acuity (BCVA), Schirmer test, breakup time, rose bengal staining score, and meibomian gland dysfunction grading. The patients were retested at the end of treatment. Results: The present study included 39 patients (30 females and 9 males). Best-corrected visual acuity was > 20/30 in >90% of patients in both groups and did not change after treatment. After treatment, improvement in ocular symptoms and meibomian gland dysfunction was more pronounced in group B (p<0.05); the other parameters did not reach statistical significance. Conclusion: Doxycycline improved meibomian gland dysfunction, ocular symptoms, and ocular surface in patients with rosacea. Even though some patients experienced worsening meibomian gland dysfunction and symptoms, no subject experienced any serious complications after administration of low-dose isotretinoin.
Keywords: Rosacea/drug therapy; Doxycycline/therapeutic use; Doxycycline/administration & dosage; Isotretinoin/therapeutic use; Isotretinoin/administration & dosage; Ocular surface; Blepharitis